Analisis kemampuan numerasi pada bangun datar di kalangan siswa sekolah menengah pertama - Kristina Warniasih; Devailin Nanda Dwi Shabila; Husnul Khotimah (Curricula: Journal of Curriculum Development, 2026)
The low numeracy skills of junior high school students remain a major challenge in Mathematics learning, particularly in plane figures material that requires conceptual understanding, procedural application, and integrated reasoning. This study aims to analyze the numeracy skills of seventh-grade students at SMPN 2 Kasihan using an open essay test. The approach in this study was a descriptive, quantitative design, with 120 students as the main participants. The instrument consisted of seven validated essay questions to measure aspects of mathematical understanding, application, and reasoning. Data were analyzed using descriptive statistics, including maximum, minimum, average, and standard deviation scores, as well as categorization of student achievement. The results showed a very significant variation in ability. Most students were in the low category, and only a few were in the very high category. The highest achievement was in understanding, while application and reasoning were still very low. These findings emphasize the need for innovative, problem-based, context-driven learning, supported by intensive remedial programs and peer tutoring, to comprehensively improve students' mathematical literacy and address the challenges of 21st-century national education.